2004
DOI: 10.1038/sj.emboj.7600508
|View full text |Cite
|
Sign up to set email alerts
|

A novel multidomain transcription coactivator SAYP can also repress transcription in heterochromatin

Abstract: Enhancers of yellow (e(y)) is a group of genetically and functionally related genes for proteins involved in transcriptional regulation. The e(y)3 gene of Drosophila considered here encodes a ubiquitous nuclear protein that has homologues in other metazoan species. The protein encoded by e(y)3, named Supporter of Activation of Yellow Protein (SAYP), contains an AT-hook, two PHD fingers, and a novel evolutionarily conserved domain with a transcriptional coactivator function. Mutants expressing a truncated SAYP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 52 publications
(57 reference statements)
0
61
0
Order By: Relevance
“…Brahma and TFIID are united by coactivator SAYP, which we have described in ref. 13. BTFly includes all subunits of TFIID and Brahma (PBAP subfamily), but not comparably abundant subunits of other coactivators, and is stable in the absence of a chromatin template according to biochemical evidence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Brahma and TFIID are united by coactivator SAYP, which we have described in ref. 13. BTFly includes all subunits of TFIID and Brahma (PBAP subfamily), but not comparably abundant subunits of other coactivators, and is stable in the absence of a chromatin template according to biochemical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…We have described a SAYP gene mutation, e(y)3 u1 , which reduces the level of SAYP (13). Close analysis of males hemizygous for e(y)3 u1 has shown that the viability of hemizygous males is decreased by 20%.…”
Section: Sayp Interacts With Tfiid and Brahma Components In Drosophilamentioning
confidence: 99%
See 3 more Smart Citations